The Relationship between Breakfast Habits and Knowledge of Nutritional Status and Learning Achievement of Class VII Students of SMPN 02 Banjar Agung, Lampung - Rahayu Yekti Maryanto (EduMatSains : Jurnal Pendidikan, Matematika dan Sains, 2024)
Breakfast is an activity that has benefits for school children which contributes energy and nutritional needs to support daily activities. Better memory is associated with increased glucose, indicating brain performance, especially those related to memory aspects. Consuming breakfast can improve cognitive learning and academic achievement. If children have good nutritional knowledge, they will determine which foods to consume that are healthy and have high nutrition. The aim of this research is to determine the relationship between breakfast habits and knowledge of nutritional status and learning achievement at SMPN 02 Banjar Agung, Lampung. The method used in this research uses descriptive analytics with a cross sectional approach. This research was conducted from June to July 2022. The number of samples in this research was 120 class VII students at SMPN 02 Banjar Agung who were filtered according to inclusion and exclusion criteria. The data was tested in the semester. This research showed that 100 people (80.0%) had good breakfast habits and 89 people (74.2%) had good learning achievements. Based on the results of the Chi Square test, the relationship between breakfast and knowledge of nutritional status obtained a p value = 0.040 (p < 0.05). The results of the Chi Square test regarding the relationship between breakfast and learning achievement obtained a p value = 0.000 (p < 0.05). It can be concluded that there is a significant relationship between breakfast and children's nutritional status and learning achievement.